PENGARUH PENGGUNAAN MEDIA SOSIAL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KELAS X IPS DI SMA NEGERI 8 PEKANBARU - Artika, Titin; Tugiman, Tugiman; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: SMA Negeri 8 Pekanbaru is one of the first high schools that started as SMPP 49 Pekanbaru, which was established in January 1976 with the Minister of Education and Culture Decree 26 November 1975 Number 0261/0/1975. This study aims to determine the effect of the use of social media on student learning outcomes in class X Ips history subjects at SMA Negeri 8 Pekanbaru. The research approach used in this research is quantitative research. Using multiple linear regression analysis and multiple linear correlation. The research methods used in this study are survey and verification methods. The subjects of this study were students of SMA Negeri 8 Pekanbaru, namely class X Ips, totaling 100 students. The results showed the value of X1 (social media youtube) obtained t_count of 0.91 with a significance value of 0.366, and the value of X2 (social media facebook) obtained t_count of -0.285 with a significance value of 0.004. This is not in accordance with the test criteria which show that the value of X1 t_count <t_tabel is 0.91 <0.1966 with a significance level of 0.366> 0.005 and X2 t_count <t_tabel namely -0.285 <0.1966 with a significance level of 0.004 <0.005 and thus can concluded that Ho's hypothesis was accepted and ha rejected, meaning Social Media (Youtube, Facebook) had no effect and was not significant on student learning outcomes.Key Words: Effects of the Use of Social Media on Learning Outcomes